THE INFLUENCE OF INFLUENCERS ON YOUTUBE SOCIAL MEDIA ON GADGET PURCHASE DECISIONS OF ECONOMIC EDUCATION STUDENTS AT SRIWIJAYA UNIVERSITY - Prasetyo Suryadi; Firmansyah; Maria Immaculata Yovita Adventy (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This study aims to analyze the influence of influencers on YouTube social media on gadget purchasing decisions among students of Economics Education at Sriwijaya University. The method used is quantitative associative with data collection techniques through questionnaires, interviews, and documentation on a sample of 77 students. The research findings revealed that influencer marketing has a significant and positive influence, with a contribution of 73.42%. Further analysis shows that influencer credibility, particularly the ability to present specific and transparent product explanations, is a key factor with a very strong percentage (83%). Meanwhile, student purchasing decisions are dominated by rational considerations, where product characteristics (89%) and reviews from other consumers (88%) are the main determining factors, overcoming the influence of mere popularity or trends. Thus, influencer marketing strategies on YouTube are proven effective in shaping purchasing decisions, especially when supported by informative, objective content that focuses on the product's utility